﻿Assessing the invasion potential of five common exotic vine species in temperate Australian rainforests - Adam Bernich; Kris French; Michael Bedward (NeoBiota, 2024)
To compare the capacity of native and exotic vine species established under a rainforest canopy, a comparison of growth rates and resource allocation was made amongst five exotic vine species that are serious and common invaders and two common native vine species under two light conditions reflective of edge and interior canopy conditions. All species experienced heavy reductions in growth parameters in the low-light treatment, but three exotic species showed stronger growth under the low light. All exotic species had higher plasticity in leaf morphology showing a significant increase in SLA under low light. Native vines may have a lower capacity to change leaf morphology in shade, as a result of local adaptation to edge habitats. Higher SLA under both low and high light conditions suggests that exotic vines species are able to exploit a range of forest conditions better than the native species. Three species, Anredera cordifolia, Araujia sericifera and Cardiospermum grandiflorum, appear particularly capable of invading rainforest interiors. Individuals produced few leaves, focusing resources on roots and stems suggesting a response to reach the canopy quickly. With their long-distance seed dispersal, plasticity in leaf SLA and high RGR, these species appear most likely to invade undisturbed rainforest.